The Effect Of Environmental Performance, Institutional Ownership Structure And Company Size On Company Value With ROE As An Intervening Variable In The Mining Sector Listed On The Indonesia Stock Exchange In 2021 - Desi Safariani; Fuad Ramdhan Ryanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine the effect of Environmental Performance, institutional ownership structure, and Company Size on company value, with ROE as an intervening variable. Based on the established sample criteria, 72 companies were obtained as research objects. Analytical techniques used include classical assumption test, multiple linear regression analysis, coefficient of determination analysis (R2), as well as F test and t test, accompanied by path analysis. The results of the path analysis showed that the variables of institutional ownership structure and Company Size directly affect the value of the company without going through ROE as an intervening variable. Meanwhile, Equation 2 shows that the relationship of these three variables to the value of the company is strong. Through a simultaneous test (F-test) for Equation 1, it was found that taken together, the variables of Environmental Performance, institutional ownership structure, and Company Size had no effect on ROE. However, in the simultaneous test for Equation 2, these variables turned out to have a significant effect on the value of the company. The partial test results (t-test) for Equation 1 showed that individually, Environmental Performance, institutional ownership structure, and Company Size had no effect on ROE. Meanwhile, for Equation 2, Environmental Performance and institutional ownership structure also do not give a significant effect on the value of the company, while the size of the company proved to give a significant effect partially.